Insubordinação de cláusulas volitivas em português brasileiro: uma abordagem funcionalista. - Baroni, Gabriela do Couto (2022)
This is a functionalist study that aims to portray the use of volitional insubordinate clauses in Brazilian Portuguese. These clauses are identical, in structural terms, to those that traditional grammars classify as “direct objective substantive subordinate clauses” and to those that functionalist studies call “direct objective completive clauses”. However, despite presenting a structure of subordination or clause complementation, insubordinate clauses are not preceded by a main clause or a matrix clause. As a corpus, 554 clauses with volitional meaning are used, collected in posts on the social networks Whastapp, Instagram and Facebook and on the internet. To support the analyses, we use, above all, the proposals of Evans (2007), Mithun (2008) and Cristofaro (2016) on the mechanisms of insubordination, and the proposal of Verstraete, D'Hertefelt and Van Linden (2012) for the types of deontic insubordination. In addition, syntactic and semantic aspects are also controlled in the data and a Perception Test is applied in order to identify whether the speaker, when reading or using, in their social networks, insubordinate clauses such as those being investigated in this study, assigns to these clauses, in fact, a volitional sense. The results indicate, in a special way, that the main mechanism of insubordination acting in the data is the ellipse (EVANS, 2007) and that, concerning the form, the volitional insubordinates in Brazilian Portuguese have different structural configurations, the most recurrent in the data collection is the structure Que + SN + Subjunctive. Lastly, the Perception Test confirms that the analyzed clauses are really identified as volitional by the speakers.